If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y + 8z = 54 Solving 6x + 3y + 8z = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y + 8z = 54 + -3y Combine like terms: 3y + -3y = 0 6x + 0 + 8z = 54 + -3y 6x + 8z = 54 + -3y Add '-8z' to each side of the equation. 6x + 8z + -8z = 54 + -3y + -8z Combine like terms: 8z + -8z = 0 6x + 0 = 54 + -3y + -8z 6x = 54 + -3y + -8z Divide each side by '6'. x = 9 + -0.5y + -1.333333333z Simplifying x = 9 + -0.5y + -1.333333333z
| 12ab-4a^2(b)=0 | | -4x-6x=10-70 | | .9+m=1.1 | | 4b+2b-4=14 | | 4x^2-5x+20-(4x^2+10x)= | | .45x+.1x=x-27 | | ((233987973*x)+(41111687*y))=1 | | 160+50w=30w+500 | | 16t^2-222-24=0 | | 4a=72*42 | | 8+3x=2x+15 | | 4x^3-5x+3x^2+6x^2-5x^3-x= | | 2(10+x)=130 | | 2(5-x)/3=-4 | | 2x^2+2x-3=3+6x | | -5t^2+37t=0 | | 40x+27=5(7x+4)+5x+7 | | 2(x-9)=y-22 | | 10-(x-3)=7(x+8) | | 28B^2+8B=0 | | 5t^2+37t+72=72 | | 2x^3-6x=-4 | | 8y+7x=-75 | | 2x^3-6c=-4 | | 5x+7(7-8x)=8x-4(8x+8) | | x/5x-4=3 | | 2(x-9)=y-26 | | (4n+5)-(-6n+7)=-15n-302 | | (7x+9)(2x-5)=0 | | 16t^2-164t-36=0 | | 10=a+15 | | 5d^2-30d+40=0 |